A Solution to the Subject(s) of Psalm 7:13–14 - Foth, Kevin (Vetus Testamentum, 2024)
The antecedent(s) of the 3ms verbal forms and 3ms pronouns in Ps 7:13–14 have long puzzled scholars, stimulating a wide range of interpretations. This article proposes a new solution, that YHWH is the subject of the first line of verse 13 and the remainder of the 3ms forms in verses 13–14 refer to the enemy of the psalmist. This solution accounts for the available data of grammar and syntax in addition to the context of the overall poem, where the description of the enemy and the actions of YHWH have verbal and thematic echoes with the content in vv. 13–14.